Perancangan Interaksi dan Antarmuka Pengguna Sistem Informasi Penjualan Produk Pada Toko Teampolos Menggunakan Pendekatan Human Centered Design (HCD) - Mohamad Rifky Pramadanianto; Ismiarta Aknuranda; Satrio Agung Wicaksono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Information technology in modern times is currently growing rapidly so that it can facilitate all human activities such as shopping through websites. The existence of a special shopping website can make it easier for humans to find or buy products quickly and can help buying and selling business actors to get maximum profit. Looking at the opportunities resulting from the development of information technology, business actors should take advantage of the momentum of using online media or web-based internet. One example of a business actor engaged in the clothing sector is Teampolos. Teampolos is a clothing retail store whose sales process is carried out online, namely using Instagram and Whatsapp, as well as offline to serve transactions with customers directly at the store. In the sales process there are obstacles such as customers looking for products displayed via Instagram that are not always complete and actual, there is limited time in serving customers on Whatsapp, and sales recap is done manually. To overcome these obstacles, a solution is proposed in the form of a website-based information system that has a user interface as the user's first glance in using it and aims to make interactions simpler in achieving goals. To design interactions and user interfaces, a Human Centered Design (HCD) approach was used with usability testing and a Single Ease Question (SEQ) questionnaire as an assessment of user convenience in testing, and chose 5 participants, namely 2 as administrators and 3 as customers. The initial design that has been completed is then tested with usability testing and SEQ questionnaires to participants who have been determined based on their respective personas. After the initial design is completed at the evaluation stage, it will enter the design improvement stage which produces two alternative versions. The first alternative on the customer side has a value of 6.36 while the administrator side has a value of 6.53, while the second alternative on the customer side has a value of 6.6 and the administrator side 6.6. So that in the second alternative design it can be said that the given task is a little easier for participants to do.